The Effect of Sovereign Sukuk, DPK, BI Rate, and NIM on Islamic Bank Profitability in Indonesia - Fikri, Shofa; Rahmawati, Anita; Afandi, Johan (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
This study aims to examine the influence of the issuance of Sovereign Sharia Securities (SBSN), Third-Party Funds (TPF), Bank Indonesia’s benchmark interest rate (BI Rate), and Net Return Margin on the profitability of Islamic banks in Indonesia. A quantitative approach is employed, utilizing statistical analysis to measure and test the relationships among variables objectively. The data used are secondary data obtained from the financial reports of Islamic banks and official publications from the Financial Services Authority (OJK), covering the period from 2017 to 2023. This time frame was chosen to provide a comprehensive overview of the trends and developments in the Islamic banking sector over the medium term. The findings reveal that all the variables studied SBSN, TPF, BI Rate, and Net Return Margin have a significant influence on the profitability of Islamic banks in Indonesia. These results highlight the importance of effectively managing these factors to enhance financial performance and competitiveness in a dynamic economic environment.